دراسة تحليلية وصفية عن الأسماء المشتقة في سورة الطارق - Suryadarma, Yoke; Abdillah, Fariz Mirza (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2018)
Linguists consider that the study of derivatives is an important subject in the study of Arabic language because it has characteristics that differ from other languages in the world. Arabic language teaching in Indonesia is widespread, this study has not been a top place among Arab students. Starting from this point of views, in this article the researcher would like to contribute the share in this study, especially on the words derivatives in Surat Al-Tarik, it becomes from this point of view, a common derivative study in the hands of Arab students as is commonly known. The researcher used qualitative research in his research, which the type of qualitative desk study is the descriptive method, and the researcher used the method of content analysis to get access to the information. The result of this research is that the derivatives names in this surah are ha>fiz{, da>fiq, qa>dir, na>s}ir, and al-ka>firi>n.